Record of Ragnarok. Volume 7 - Umemura, Shin'ya; Fukui, Takumi (Viz signature., 2023)
"Humanity's greatest heroes battle the gods for the survival of the human race! Once every millennium, the gods assemble to decide if humanity is worthy of its continued existence or if it should be destroyed! When the verdict is destruction, the final battle between the gods and mortal heroes will decide the survival or extinction of the human race--a battle known as Ragnarok! Humanity's most notorious murderer, Jack the Ripper, has proved to be an unexpectedly clever and difficult opponent for the heroic Heracles. Their battle through the dark streets of 19th-century London takes more than a few surprising turns, until Jack actually manages to sever Heracles's arm! The watching crowd is stunned and outraged--how can this be? Heracles realizes he really needs to pull out all the stops to win, but Brunhilde's twisted champion has more tricks up his sleeves..."--Publisher.